SURVEI TINGKAT KEMAMPUAN VO2 MAX WASIT PENGPROV PERBASI KALIMANTAN BARAT - Wisnu Saputra; Andika Triansyah; Mimi Haitami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractProblems in Singer Research were VO_2 Max basketball referees who have not been investigated in West Kalimantan carefully investigated operating data and facts that are very vital endurance capabilities that must be possessed so that they can reduce fatigue levels which means. The aim of the study was to determine the ability of the maximum Oxygen Volume VO_2 basketball referee in the West Kalimantan professors This study used a descriptive method with a test survey method. The study population was all pengprof referees who were clearly 24 referees. Sampling in this study using total sampling technique. Of the 24 samples above VO_2 Max are very good, good, sufficient, and moderate. The test and measurement techniques were carried out by multistage running (multistage fitness test) to measure VO_2 Max. Based on the results of the study, the conclusions were obtained as follows; Physical Ability Pengprof basketball referee From 24 ball referees That we the Good category There we 3 With a percentage of 12.5% in the category of Pretty 17 Referees with a percentage of 70.83% and the category of Less as 4 Referees with a percentage of 16.6% and an average value of 86 conclusions the researcher can say that there we still a need for physical training to add VO2 MAX referee referees who were in Kalimantan when leading a match it will diminish its fatigue. Keyword: Basket, Vo2max, wasit